The significance of enzyme histochemical patterns in carcinomas of the large intestine in man. Issue 6 (June 1973) - McGinty, F.; Delides, G.; Harrison, D.
Abstract : The activities of 13 enzymes in 40 carcinomas of the large bowel have been studied using histochemical techniques. Five enzymes—non-specific esterase, monoamine oxidase, succinate dehydrogenase, cytochrome oxidase, and acid phosphatase—commonly show much less activity in the tumours than in adjacent normal colon. The tumours have been classified based upon the number of enzymes which show marked reduction in activity in each tumour (types 1-5). The enzyme histochemical type and the size of the tumours have been jointly correlated with the presence of lymph node metastasis. Small type 1 or 2 tumours do not appear to be associated with metastatic disease. Small type 5 tumours were commonly associated with secondary carcinoma in the lymph nodes. Large tumours (greater than 25 sq cm surface area) of any histochemical type were frequently associated with lymph node metastasis. Discussion of the possible reasons for these findings and their clinical significance is presented.